Thioacetamide as an Ammonium Source for Multicomponent Synthesis of Pyridines from Aldehydes and Electron-Deficient Enamines or Alkynes - Wan, Jie-Ping; Zhou, Youyi; Jiang, Kezhi; Ye, Hongyan (Synthesis, 2014)
A generally applicable multicomponent method has been established for the synthesis of pyridines. In the reactions, thioacetamide is used as a cheap and efficient ammonium source in a multicomponent reaction with aldehydes and electron-deficient enamines or alkynes to give 3,4,5-trisubstituted pyridines in moderate to good yields and with a high product diversity.
Keywords: multicomponent reactions; ring closure; pyridines; aldehydes; enamines; alkynes